The Battles of the Umayyads: Remembering War from West to East - Albarrán Iruela, Javier (Der Islam, 2023)
The memory of war - and the use of this - is a constant in the Middle Ages and beyond. Within all this war memory, the remembrance of great battles is, perhaps, the most recurrent phenomenon. The pitched battle had an extraordinary impact on the people of the time, which made its remembrance remain alive and dynamic in the collective memory, as moments when the balance of power was seen to have tipped, or when aspects of collective identity were shaped. The battles became places of memory. This paper studies the memory circulating in Umayyad al-Andalus about the battles of their ancestors, the eastern Umayyads. Focusing on Ḥunayn and Marj Rāhiṭ, the two "eastern" battles most remembered in Umayyad al-Andalus and both with important implications for their dynastic history, this paper analyzes how this memory is presented, how these battles are "memorialized" and "commemorated" through texts and rituals, in what contexts of memory production they appear, and for what purposes.